The Impact of Rastra-BPNT Assistance on Household Food Expenditure Patterns and Poverty Status in Indonesia - Fardian, M Iqbal; Nazer, M; Muharja, Fajri (Jurnal Informatika Ekonomi Bisnis, 2024)
This study uses Susenas March 2019 raw data in a cross-section of 34 provinces and 514 districts/cities in Indonesia with a coverage of 315,672 households, designed using a quasi-experiment on the treatment group and control group after program implementation. The treatment group was formed by beneficiary families while the control group was formed by non-beneficiary families. The sample of beneficiaries was 50,485 or 9,845,922 households if calculated with Susenas weighting (65.55% of the total 2019 realization of 15,020,323 national beneficiaries) and non-beneficiaries were 181,358 households. The data were analyzed using a probit regression model and impact estimation was conducted using the Propensity Score Matching (PSM) approach. The results suggest that education level is a bigger determinant for households to become Rastra-BPNT beneficiaries, especially for household heads who did not finish primary school and those who graduated from primary school. Rastra-BPNT food social assistance has a significant and positively correlated impact on beneficiary families with a pattern of food proportion to total expenditure > 50%. There was a shift in the food consumption budget share for Beneficiary Families in several dominant commodities such as grains; eggs and milk; processed food and beverages; and cigarettes, tobacco and betel. The distribution of Rastra-BPNT from November 2018 to February 2019 can reduce the gap between household groups, but there are still errors in the distribution of benefits.